6 - Genre, handicap et santé sexuelle et reproductive au Cameroun : implication des acteurs sociaux et rapports aux politiques publiques - Magne, Estelle Kouokam; Kuetche, Irène Flore Chiewouo; Djoukouo, Félicité (Journal of Higher Education in Africa, 2022)
Based on interviews with leaders of civil society organisations working for the protection of people with physical and visual disabilities, this article examines the involvement of socio-political actors in promoting the sexual and reproductive health of people with disabilities, as well as the participation of civil society organisations (CSOs) in public action on sexual and reproductive health (SRH). This study admits that people with disabilities are sexually active, have a marital life, and have very specific sexual and reproductive health needs. These needs are superficially taken into account both by the associations and public health policies. A low level of involvement which perpetuates the feeling of stigmatisation and exclusion of people with disabilities (PWDs) among the various stakeholders in the process of implementing public health policies in Cameroon.